The amino-terminal domain of LexA repressor is alpha-helical but differs from canonical helix-turn-helix proteins: a two-dimensional 1H NMR study. - Lamerichs, R M (1989)
The amino-terminal DNA binding domain of LexA repressor consisting of 84 amino acid residues has been studied by two-dimensional 1H NMR. Sequence-specific 1H resonance assignments were made for the first 60 amino acid residues. The secondary structure of this part of the protein contains three alpha-helices in the peptide segments 8-20, 28-35, and 41-54. The last helix has a distortion around residues 47-48. The peptide segment 28-47 shows weak homology with other helix-turn-helix proteins. To investigate the spatial structure of this region of the molecule distance-geometry calculations were performed based on proton-proton distance constraints from nuclear Overhauser effects. The resulting structure shows that the segment 28-47 contains two helices with a loop region between them. The relative orientation of the two helices is similar to that found in helix-turn-helix proteins, but the helices are further apart, with the phenyl ring of Phe-37 located between them. The Brookhaven Protein Data Bank was searched for structurally homologous peptide segments in other proteins. The result of this search was that the two-helical structure of LexA is not more closely related to the canonical helix-turn-helix motif than it is to similar substructures found in other classes of proteins.